Effect of Annealing Times on the Structural and Optical Properties of PbO Thin Films Prepared by D.C Sputtering - Rauuf, Aws Faisal; Aadim, Kadhim A. (Iraqi Journal of Science, 2023)
In this work, lead oxide (PbO) thin films were deposited using D.C. sputtering method on a surface of glass substrates and then thermally annealed at a temperature of 473K with annealing times of (1,2 and 3) hours. The structural, morphological, and optical properties of films were determined using X-ray diffraction (XRD), atomic force microscopy (AFM), FT-IR, and UV-Visible spectroscopy. The structure studies confirmed that PbO films are polycrystalline structures in an orthorhombic phase with average grain size (24.51, 29.64, 46.49, 16) nm with increasing annealing time. From AFM, the roughness of the film surface  (3.26, 1.76, 1.61, 1.79) nm as the film annealing time increases. The optical band gap values of the PbO thin films are (3.9, 2.8, 3.7, 2.4) eV as the annealing time increases.